Characterization and quantification of proteins secreted by single human embryos prior to implantation. Issue 11 (16th October 2015) - Poli, Maurizio; Ori, Alessandro; Child, Tim; Jaroudi, Souraya; Spath, Katharina; Beck, Martin; Wells, Dagan
Abstract: The use of in vitro fertilization (IVF) has revolutionized the treatment of infertility and is now responsible for 1–5% of all births in industrialized countries. During IVF, it is typical for patients to generate multiple embryos. However, only a small proportion of them possess the genetic and metabolic requirements needed in order to produce a healthy pregnancy. The identification of the embryo with the greatest developmental capacity represents a major challenge for fertility clinics. Current methods for the assessment of embryo competence are proven inefficient, and the inadvertent transfer of non‐viable embryos is the principal reason why most IVF treatments (approximately two‐thirds) end in failure. In this study, we investigate how the application of proteomic measurements could improve success rates in clinical embryology. We describe a procedure that allows the identification and quantification of proteins of embryonic origin, present in attomole concentrations in the blastocoel, the enclosed fluid‐filled cavity that forms within 5‐day‐old human embryos. By using targeted proteomics, we demonstrate the feasibility of quantifying multiple proteins in samples derived from single blastocoels and that such measurements correlate with aspects of embryo viability, such as chromosomal (ploidy) status. This study illustrates the potential of high‐sensitivity proteomics to measure clinically relevant biomarkers in minute samples and, more specifically, suggests that key aspects of embryo competence could be measured using a proteomic‐based strategy, with negligible risk of harm to the living embryo. Our work paves the way for the development of "next‐generation" embryo competence assessment strategies, based on functional proteomics. Synopsis: To maximise in vitro fertilization success rate, the embryo prioritized for transfer must be the most capable within the cohort of embryos generated by the patient. The blastocentesis procedure described here could be a way to get there. Blastocentesis is a novel micromanipulation technique used to collect a 4 nL sample of blastocoelic fluid from living human embryos. A catalogue of 182 proteins secreted by the human blastocyst and validated by microarray gene expression analysis of whole human embryo is provided. Targeted mass spectrometry approach enables the measurement of nine proteins of interest from single human blastocoels. Blastocentesis has no long‐term impact on embryo overall architecture, suggesting its potential application in a clinical setting. Abstract : To maximise in vitro fertilization success rate, the embryo prioritized for transfer must be the most capable within the cohort of embryos generated by the patient. The blastocentesis procedure described here could be a way to get there.